HUBUNGAN KECERDASAN EMOSIONAL DENGAN NILAI OBJECTIVE STRUCTURED CLINICAL EXAMINATION (OSCE) MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS RIAU ANGKATAN 2011 - Frida Septiani Tavia; Zulharman "; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
The Objective Structured Clinical Examination (OSCE) is evaluated in Faculty of Medicine University of Riau as one of a learning achievement. The success of OSCE is influenced by internal and external factors, one of internal factors is emotional intelligence. High emotional intelligence can improve a learning achievement on a student. The purpose of study was to determine the relation of emotional intelligence and OSCE score in medical students of Riau University batch 2011. This research used analytic method of retrospective study. The population was students at Faculty of Medicine University of Riau batch 2011. Samples of this research were 115 students with total sampling method. This research used a questionnaire based on the theory of Goleman’s emotional intelligence. The relation of emotional intelligence and OSCE score was analyzed using Somers’d test. The result of the study didn’t show a relation between emotional intelligence and OSCE score (p=0,407). In conclusion there was no relation between emotional intelligence and OSCE score in medical students of Riau University batch 2011.Keywords: emotional intelligence, objective structured clinical examination